Printed publications and public organizations of polish-lithuanian tatars: the second half of the 19th century and the 20th century (Herald of Journalism, 2021)
At the end of the 19th and the beginning of the 20th century, there was a national revival of the Polish-Lithuanian Tatars connected with the general atmosphere in Europe where nationalism was a key ideology, as well as with the increase of the national feelings among the Muslim nations of the Russian Empire, and with the effort of a group of Polish Tatar young intellectuals.The purpose of the article is to present the results of research on the content of the media, literature and cultural values of the Polish-Lithuanian Tatars in Russia in the late nineteenth and early twentieth centuries.In Saint Petersburg, at the end of the 19th century, there was a quite large settlement of the Polish and other inhabitants of the Empire. According to the statistical data, in 1900, there were 50,000 Poles living there, that stood for 3,57% of the city population. The same statistics shows that there were about 5,800 Tatars from Crimea, the Volga Region, and Siberia settled in Saint Petersburg. In these numerous national mosaics there also were the Polish-Lithuania Tatars.In Saint Petersburg, activists of national Pan-Turkism and Pan-Islam movements in Russia were educated. Among them one could also find Polish-Tatar students from such families as Achmatow- icz, Kryczyński, Sulkiewicz, Bazerewski, et al. At that time, at the beginning of the 20th century, Leon Kryczyński began to be an organizer and leader. He descended from the old, landowner Tatar knez (royal) family of Najman Mirza Kryczyński, originated from the knez family of Nejman-Piotrowicz, one of the oldest Tatar aristocratic family of the Grand Duchy of Lithuania.Key words: Polish-Lithuanian Tatars, ideology, national feelings, Russian Empirе, intelligence.